2020
DOI: 10.1021/acsami.9b20531
|View full text |Cite
|
Sign up to set email alerts
|

Bi-Cation Electrolyte for a 1.7 V Aqueous Zn Ion Battery

Abstract: Rechargeable aqueous zinc-ion batteries (ZIBs) are receiving increased attention because of their high safety and low cost. However, their practical application is plagued by their low energy density as a result of low output voltage and a narrow voltage window of aqueous electrolytes. Here, we explored a ZIB with a wider potential window using bication (1 M Al­(CF3SO3)3/1 M Zn­(CF3SO3)2) as the electrolyte and α-MnO2 as the cathode, obtaining a discharge voltage of 1.7 V, ∼0.3 V higher than the value reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
97
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(103 citation statements)
references
References 31 publications
6
97
0
Order By: Relevance
“…The proposed methods involve adding organic and inorganic additives, and exploring concentrated electrolytes. 41,93 The working mechanism of these solutions is stabilizing the water molecules via hydrogen bonds, coordination, and so on. As shown in Figure 6E, Huang et al 41 immobilized the water molecules by adding a thickening agent, fumed silica (FS).…”
Section: Anode Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…The proposed methods involve adding organic and inorganic additives, and exploring concentrated electrolytes. 41,93 The working mechanism of these solutions is stabilizing the water molecules via hydrogen bonds, coordination, and so on. As shown in Figure 6E, Huang et al 41 immobilized the water molecules by adding a thickening agent, fumed silica (FS).…”
Section: Anode Activitymentioning
confidence: 99%
“…A hybrid electrolyte composed of 1 M Al(CF 3 SO 3 ) 3 and 1 M Zn (CF 3 SO 3 ) 2 was proposed, in which the introduction of Al 3+ could coordinate with solvent molecules to decrease their chemical activity, leading to a broader electrochemical window. 93 As a kind of concentrated electrolyte, "Water-in-salt" electrolyte has attracted intensive attention in recent years. 88,[94][95][96] This type of electrolyte demonstrates great potential in preventing the corrosion and HER as it has few free water molecules to participate in side reactions.…”
Section: Anode Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Liu et al reported that the electrochemical window of the ZnÀ MnO 2 battery with the alkaline anolyte and the acidic catholyte was broadened to 3 V owing to the high overpotentials of gas evolution in alkaline/acidic conditions, and this battery can output a high voltage of 2.44 V. [18] And a novel bication electrolyte (1 M Al (CF 3 SO 3 ) 3 + 1 M Zn(CF 3 SO 3 ) 2 ) was employed in aqueous ZnÀ MnO 2 batteries to adjust the intermediate species upon charging/discharging, which is intensively associated with voltage, and fianally a high discharge voltage of 1.7 V was obtained due to the formation of the unique Al x MnO 2 species, accompanied with the expansion of the operation voltage window from 1.5 to 1.9 V owing to the suppression of gas evolution by the Al(CF 3 SO 3 ) 3 component. [19] In order to improve the reaction kinetics and structural stability of MnO 2 cathode, clever designs of composite structure are proposed with the aim to provide highly conductive network, more active sites for charge storage, void space to accommodate the volumetric change and/or self-adhesive configuration forming a free-standing electrode. For example, three-dimensional (3D) micro-flowers composed of MnO 2 nanowires dispersed within graphene nanosheets deliver an excellent electrochemical performance because of the large internal space within micro-flowers, 3D fast electron/cation migration pathways and stable structural integrity from the robust skeleton.…”
Section: Advances In Science and Technology To Meet Challengesmentioning
confidence: 99%
“…reported that the electrochemical window of the Zn−MnO 2 battery with the alkaline anolyte and the acidic catholyte was broadened to 3 V owing to the high overpotentials of gas evolution in alkaline/acidic conditions, and this battery can output a high voltage of 2.44 V [18] . And a novel bication electrolyte (1 M Al(CF 3 SO 3 ) 3 +1 M Zn(CF 3 SO 3 ) 2 ) was employed in aqueous Zn−MnO 2 batteries to adjust the intermediate species upon charging/discharging, which is intensively associated with voltage, and fianally a high discharge voltage of 1.7 V was obtained due to the formation of the unique Al x MnO 2 species, accompanied with the expansion of the operation voltage window from 1.5 to 1.9 V owing to the suppression of gas evolution by the Al(CF 3 SO 3 ) 3 component [19] …”
Section: Zn−mno2 Batteriesmentioning
confidence: 99%